ANALYSIS OF THE INFLUENCE OFFINANCING TO DEPOSIT RATIO, OPERATIONAL COSTS ON OPERATIONAL INCOME, NON PERFORMING FINANCING, THIRD PARTY FUND PROFITABILITY, CAPITAL ADEQUANCY RATIO, PROPORTION OF INDEPENDENT COMMISSIONERS AS MODERATING VARIETIES OF SHARIA B - Mesakh, Januardi (Asosiasi Dosen Akuntansi Indonesia, 2019)
Profitability is the ability of a company to generate profits which is a comparison between net income after deducting interest and tax expenses (Earning After Taxes / EAT) which is generated from the company's principal activities with total assets (assets ) owned by the company to carry out company assets as a whole and expressed as a percentage. This study aims to examine the effect of Financing to Deposit Ratio (FDR),Operating Costs on Operating Income (BOPO),  Non Performing Financing (NPF), Third Party Funds (TPF),  Capital Adequacy Ratio (CAR)to Profitability with the Independent Board of Commissioners Proportion (PDKI) as a moderating variable. This type of research is causal. The population in this study amounted to 10 Sharia Banks registered at Bank Indonesia in 2012-2016. The sampling method is census, so that the number of samples used is 50 sample data. The results showed simultaneously, all independent variables had a significant effect on profitability, but partially only thevariables Financing to Deposit Ratio (FDR)and Third Party Funds (DPK)had a positive effect on profitability. While Operational Costs Against Operating Income (BOPO), Non Performing Finance (NPF)and Capital Adequacy Ratio (CAR)do not affect profitability. The proportion of Independent Commissioners (PDKI) is not a moderating variable in this study.